2016
DOI: 10.1002/jnr.23805
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dots and potential therapy for Krabbe's disease

Abstract: Enzyme replacement therapy and substrate reduction therapy have proved useful in reversing many pathological consequences of many non-neural lysosomal storage diseases but have not yet reversed pathology or influenced disease outcome in Krabbe disease, We will discuss the relative merits of stem cell therapy, molecular chaperone therapy, gene therapy, substrate reduction therapy, enzyme replacement therapy and combination therapy. Given the limitations of these approaches we will introduce the idea of using ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Delivery vehicles such as nanoparticles 13 , extracellular vesicles 79 , polymersomes 80,81 and quantum dots 82 have been explored to improve enzyme delivery to the CNS in LSDs. Whilst quantum dots have only been investigated in an in vitro setting 82 , successful in vivo studies have been conducted with polymersomes 81 , extracellular vesicles 79 and nanoparticles; of these, nanoparticles have been researched most extensively.…”
Section: Delivery Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Delivery vehicles such as nanoparticles 13 , extracellular vesicles 79 , polymersomes 80,81 and quantum dots 82 have been explored to improve enzyme delivery to the CNS in LSDs. Whilst quantum dots have only been investigated in an in vitro setting 82 , successful in vivo studies have been conducted with polymersomes 81 , extracellular vesicles 79 and nanoparticles; of these, nanoparticles have been researched most extensively.…”
Section: Delivery Vehiclesmentioning
confidence: 99%
“…Delivery vehicles such as nanoparticles 13 , extracellular vesicles 79 , polymersomes 80,81 and quantum dots 82 have been explored to improve enzyme delivery to the CNS in LSDs. Whilst quantum dots have only been investigated in an in vitro setting 82 , successful in vivo studies have been conducted with polymersomes 81 , extracellular vesicles 79 and nanoparticles; of these, nanoparticles have been researched most extensively. Multiple studies have employed nanoparticles to successfully deliver therapeutic enzymes to the CNS of Gaucher disease 83 , Krabbe disease 84 and MPS II murine models, reporting reduction of storage products to non-pathological levels 85 (for a thorough review of the role of nanoparticles in LSD treatment up to 2016, please refer to Martin-Banderas et al 13 ).…”
Section: Delivery Vehiclesmentioning
confidence: 99%
“…13 Furthermore, the small hydrodynamic size (10–20 nm) of functionalized QDs has been reported to be suitable for neuron and glial cell labeling and tracking. 1415 QD applications in the brain have been widely explored in both fundamental research as well as in clinical investigation, 1623 correlating with the interest in using functionalized QDs as drug-delivery vehicles or targeted-imaging biomarkers for central nervous system (CNS) diseases. Previous literature has shown that chemically modified QDs can deliver drugs and peptides to the developing brain.…”
Section: Introductionmentioning
confidence: 99%